Exploring barriers to primary care for migrants in Greece in times of austerity: Perspectives of service providers. (2nd October 2017) - Papadakaki, Maria; Lionis, Christos; Saridaki, Aristoula; Dowrick, Christopher; de Brún, Tomas; O'Reilly-de Brún, Mary; O'Donnell, Catherine A; Burns, Nicola; van Weel-Baumgarten, Evelyn; van den Muijsenbergh, Maria; Spiegel, Wolfgang; MacFarlane, Anne
Abstract: Background: Migration in Europe is increasing at an unprecedented rate. There is an urgent need to develop 'migrant-sensitive healthcare systems'. However, there are many barriers to healthcare for migrants. Despite Greece's recent, significant experiences of inward migration during a period of economic austerity, little is known about Greek primary care service providers' experiences of delivering care to migrants. Objectives: To identify service providers' views on the barriers to migrant healthcare. Methods: Qualitative study involving six participatory learning and action (PLA) focus group sessions with nine service providers. Data generation was informed by normalization process theory (NPT). Thematic analysis was applied to identify barriers to efficient migrant healthcare. Results: Three main provider and system-related barriers emerged: (a) emphasis on major challenges in healthcare provision, (b) low perceived control and effectiveness to support migrant healthcare, and (c) attention to impoverished local population. Conclusion: The study identified major provider and system-related barriers in the provision of primary healthcare to migrants. It is important for the healthcare system in Greece to provide appropriate supports for communication in cross-cultural consultations for its diversifying population.